Sequencing of game complexes in women’s volleyball: are there differences according to the set played? - Pedro Henrique Cavalcante Vieira; Lorenzo Laporta; Gustavo Ferreira Pedrosa; Augusto Faria de Paula Santana; Auro Barreiros Freire; Crislaine Couto Rangel; Claudio Andre Barbosa de Lira; Filipe Manuel Clemente; Thiago José Leonardi; Gustavo De Conti Teixeira Costa (Human Movement)
Purpose The objective of the present manuscript was to analyse the flow of play in high-level women’s volleyball by sequencing game complexes per set.